Analisis Sistem Pengupahan “Bawon” pada Pertanian Padi (Studi Kasus pada Petani di Desa Gambar Kecamatan Wonodadi Kabupaten Blitar) - Dwi Wahyuni (Universitas Muhammadiyah Sidoarjo, 2016)
As an agricultural country, agricultural sector plays an important role in the Indonesia economic life, especially in rural areas. Farm laborers as one component of the agricultural sector, have a considerable contribution in determining the success of this sector. But there are unique facts occur in Blitar Regency, one of which happened in Gambar, Wonodadi District, Blitar Regency related to wage system called